Multidrug resistant clinical strains isolated from tracheal aspirates of patients in Dhaka, Bangladesh - Afroz, Jinia; Jubyda, Fatema T.; Sharmin, Sanzida; Faruq, Md. J.; Dey, Amit K.; Ibrahim, Md.; Farzana, Tasmia; Sarkar, Murshed H. (International Journal of Research in Medical Sciences, 2020)
Background: Antimicrobial resistance poses a major threat in the treatment of respiratory disease especially in developing countries like Bangladesh. Multidrug-resistant (MDR) bacteria along with extremely drug resistant (XDR) bacteria have emerged as major clinical and therapeutic dilemma in the treatment of tracheal infections here. Thus, the aim of this study is to assess multidrug resistance among clinical strains isolated from tracheal aspirates of patients in Dhaka, Bangladesh. Methods: Total 200 clinical isolates from tracheal aspirates were identified and their antibiotic susceptibility profiles were evaluated by using the VITEK 2 system following the Clinical and Laboratory Standards Institute guidelines. Patient information on diagnosis, sex, age was obtained from hospital data. Results: Of 200 clinical isolates obtained, Pseudomonas aeruginosa was the most frequent pathogens (30.5%) followed by Acinetobacter baumannii (29%), Klebsiella pneumoniae (22.5%), Streptococcus pneumoniae (7.5%), Escherichia coli (5%), Staphylococcus aureus (2%), Proteus spp (1.5%), Enterobacter spp (1%), Citrobacter spp (0.5%), Providencia spp (0.5%). Of 20 different antibiotics tested, highest number of isolates (86%) showed resistance to third generation cephalosporin cefixime, however least number of isolates showed resistance to polymixin antibiotics- colistin (12.5%) and polymixin B (6%). Tracheal infection was found to be more prevalent in males rather than in females although this difference was not statistically significant. The prevalence of infections was highest among the patients of age-group (old adults) ≥60 years (61.5%). Of 200 clinical isolates, 43 (21.5%) were XDR and 125 (62.5%) were MDR bacteria. Of 200 clinical isolates, the synthesis of extended spectrum β-lactamases (ESBL) and carbepenemase were detected in 59 (29.5%) and 98 (49%) strains respectively. Conclusions: Tracheal infections caused by β-lactamase producing MDR and XDR pathogens among patients are high in Dhaka, Bangladesh. Therefore, there is an urgent need for constant surveillance and interventions in Bangladesh in order to prevent further spreading of those resistant organisms.